Uso da reidratação para reduzir a perda pós-colheita de salsa (Petroselinum crispum Mill. Nym.) - Garcia de Oliveira , Vitor; Daniel Pereira de Souza , Lucas; Candido Panarotto , Victoria; Cristina Silva Ribeiro , Fernanda (ANAIS DO ENIC, 2026)
-